National Accounts Studies of the Arab Region, Bulletin No. 32 - United Nations Economic; Social Commission for Western Asia (United Nations, 2013)
This publication presents available data and estimates of GDP at both current and constant prices, in addition to the consolidated national accounts for each Arab Region member country during a five years period, and the estimated real GDP growth for year of publication. It is a reference for accurate, reliable data and statistical indicators from national sources covering entire Arab region and intended for the public and private sectors, experts and researchers in the field and regional and international organizations.